Joint Transmit Antennas for Energy Efficiency in Downlink Massive MIMO Systems - Salh, Adeeb; Audah, Lukman; Mohd Shah, Nor Shahida; Hamzah, Shipun Anuar (International Journal of Integrated Engineering, 2018)
Massive multiple-input-multiple-output (MIMO) systems are an exciting area of fifth-generation (5G) technology and very important in maximizing energy efficiency (EE) and saving battery technology.  Obtaining energy efficiency without sacrificing the quality of service (QoS) has become increasingly important for mobile devices. In this paper, we investigate the maximal EE for downlink massive MIMO systems using zero-forcing beamforming (ZFBF), dependent on the number of antenna elements and the optimal number of users inside the cell to optimize the transmit power. The linear precoding ZFBF is able to mitigate interbeam interference, in addition to noise, due to expanding the reception at low  power transmission.  The simulation results reveal that the maximal energy efficiency  can be obtained dependent on increasing the number of antennas M and choosing the  , where the number of antennas is greater than the critical number of antennas   , which minimizes the received interference due to increased transmit power.